STUDI KOMPARASI HASIL BELAJAR IPS DENGAN MENERAPKAN METODE ROLE PLAYING DAN METODE CERAMAH BERVARIASI DALAM PEMBELAJARAN IPS SISWA KELAS VII SMP NEGERI 2 JAKENAN KABUPATEN PATI - Yulianto, Lilik; ., Tukidi (SOSIOLIUM : Jurnal Pembelajaran IPS, 2020)
Based on the fact in the field that the students learning outcomes using a variety of lectruring methods on social science learning proces are not yet completely succes. The aim of this research is to know the students learning aoutcomes comparation between role playing method and lecturing methods on social science learning proces of first grade students of junior high school 2 Jakenan Pati. The result of this study shows that there are a significant differenciation on students learning outcomes of experimental group compared control group. The afective obeservation result is on 16,58 range score which means being in a medium category and the control group is on 16,26 range score which means in a medium category too. Based on t-test results , the deviation score between the learning outcomes on experimental group and control group is 3,249 , score of thitung > ttabel (3,249>2,397). The experimental group got an increasing learning outcomes range on 22,76 and 10,69 for the control group.